Quantitative measurements of joint mobility in adolescents. Issue 2 (April 1984) - Fairbank, J C; Pynsent, P B; Phillips, H
Abstract : Six measurements of joint mobility were made in a group of 446 normal adolescents. A method of measuring hip and knee rotation is presented. All these data are normally distributed, and would suggest that joint hypermobility lies at the end of the normal spectrum. There was a weak but significant correlation between each of the different measures of joint mobility except elbow hyperextention. Criteria for joint laxity are discussed in this age group, and the importance of quantitative techniques of measuring joint mobility are emphasised.